Hoo Leony Gracia Budi Saputra PELATIHAN BATIK TULIS DAN TEKNIK JUMPUTAN BAGI MASYARAKAT BANYU URIP LOR SURABAYA - Hoo Leony Gracia Budi Saputra; Kelvin Marcellino Ibrahim (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2020)
Batik is a pictorial fabric that is known for its unique motifs, variety of styles and colors. The process ofmaking batik is quite complicated and required specific expertise. Batik itself has become a distinctivefeature of Indonesian state, with October 2 celebrated as national batik day. The development of batik itselfis not only in one or two regions, but almost every region in Indonesia had batik with their own unique characteristics.In addition, the development of batik is not only inside the country, but foreign people also takeinterest on the development of batik. Batik could be preserved with a variety of efforts, one of them is byholding batik training for the general public. This made not only batik craftsmen can make batik, but thegeneral society can also do it. Surely this will make a huge contribution for the general society towards thepreservation of Indonesian’s batik. Therefore, the reason for holding “batik tulis” and “jumputan” techniquetraining for Banyu Urip Lor Surabaya village is to introduce the process of making a batik and participate in thepreservation of batik.